Biomass and cardboard waste-based briquettes for heating and cooking: Thermal efficiency and emissions analysis. (15th November 2022) - Ferronato, Navarro; Calle Mendoza, Iris Jabneel; Ruiz Mayta, Jazmín Gidari; Gorritty Portillo, Marcelo Antonio; Conti, Fabio; Torretta, Vincenzo
Abstract: Waste-based briquettes can be an alternative option that can foster the reduction of waste inflow into final disposal sites and introduce alternative energy sources for cooking and heating in rural areas. In particular, the assumption of waste-based briquettes in Andean areas can be of higher potential, due to the lack of biomass sources locally available and the low environmental temperature that increases the requirements of heating systems. The current research would provide a contribution to the scientific literature by introducing a combustion analysis at 3300 m above the sea level for comparing the thermal efficiency and emissions of sawdust and cardboard waste-based briquettes with conventional firewood for heating and cooking purposes. Laboratory tests were carried out for estimating five combustion efficiency parameters, as well as CO, CO2, and PM2.5 emissions. Results suggested that 80% cardboard and 20% sawdust briquettes increase the boiling time of water by about 30–50% compared to firewood, due to the lower combustion power (−44%). On the other hand, the thermal efficiency increases of about 10–13%, while biomass consumption and energy consumption per minute decrease by about 27% and 44%, respectively. In addition, emissions reduce compared to firewood, from 32.6 g CO kg −1 to 22.9 g CO kg −1 and from 1260 mgPM2.5 kg −1 to 933 mgPM2.5 kg −1 . On balance, the research demonstrates that non-recyclable cardboard waste obtained from separate collection and discarded sawdust from sawmills can be employed for briquettes production as alternative fuels for heating systems in Andean rural areas, contributing to reducing waste final disposal and boosting circular systems. Highlights: Firewood and cardboard waste-based briquettes combustion evaluations are conducted. 20% sawdust - 80% cardboard waste briquettes achieved higher thermal efficiency. PM2.5 emissions are considerably lower for 80% cardboard waste briquettes. Cardboard based briquettes can be a potential alternative fuel for the Andean area.